2022
DOI: 10.3389/fimmu.2022.1013542
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus infection can alter the level of tumour stemness and T cell infiltration in patients with head and neck squamous cell carcinoma

Abstract: Head and neck squamous cell carcinoma (HNSCC) usually has a poor prognosis and is associated with a high mortality rate. Its etiology is mainly the result from long-term exposure to either alcohol, tobacco or human papillomavirus (HPV) infection or a combination of these insults. However, HNSCC patients with HPV have been found to show a survival advantage over those without the virus, but the mechanism that confers this advantage is unclear. Due to the large number of HPV-independent HNSCC cases, there is a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
(29 reference statements)
1
1
0
Order By: Relevance
“…Our study showed that there is no difference in the level of infiltration of naïve B cells and B cell memory cells between the two clusters, while the level of infiltration of CD8 T cells, follicular helper T cells, Tregs, resting NK cells, and activated NK cells of the C1 subtype is much higher than that of the C2 subtype. These results implied that cell immunity plays an important role in the antitumor immune response, and high expression of CD8 T cells and NK cells is associated with a good prognosis, which remains consistent with previous findings [ 41 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our study showed that there is no difference in the level of infiltration of naïve B cells and B cell memory cells between the two clusters, while the level of infiltration of CD8 T cells, follicular helper T cells, Tregs, resting NK cells, and activated NK cells of the C1 subtype is much higher than that of the C2 subtype. These results implied that cell immunity plays an important role in the antitumor immune response, and high expression of CD8 T cells and NK cells is associated with a good prognosis, which remains consistent with previous findings [ 41 43 ].…”
Section: Discussionsupporting
confidence: 92%
“…This may be attributed to the predominant utilization of mRNA data in those present analyses. With the recent emergence of single‐cell sequencing, undoubtedly, a plethora of novel biomarkers will be discovered 44,45 . The integration of single‐cell sequencing with deep learning networks holds promising prospects for exploring high‐performance biomarkers.…”
Section: Hpv‐associated Cancersmentioning
confidence: 99%